Kongo : power and majesty - Giuntini, Christine; Green, James, 1987-; Howe, Ellen G.; Rizzo, Adriana; Windmuller-Luna, Kristen; LaGamma, Alisa; Martin, Phyllis; Thornton, John K. (John Kelly), 1949-; Blackmore, Josiah, 1959-; Metropolitan Museum of Art (New York, N.Y.) (2015)
"A landmark presentation that will radically redefine our understanding of Africa's relationship with the West, Kongo: Power and Majesty, opening at The Metropolitan Museum of Art this September, will focus on one of the continent's most influential artistic traditions, from the earliest moment of direct engagement between African and European leaders at the end of the 15th century through the early 20th century. The creative output of Kongo artists of Central Africa will be represented by 134 works drawn from more than 50 institutional and private collections across Europe and the United States, reflecting five hundred years of encounters and shifting relations between European and Kongo leaders. From a dynamic assembly of 15 monumental power figures to elegantly carved ivories and finely woven textiles, the exhibition will explore how the talents of Central Africa's most gifted artists were directed toward articulating a culturally distinct vernacular of power."--Metropolitan Museum of Art website.
Map of Africa -- Chronology of kingship -- Kongo : power and majesty / Alisa LaGamma -- The Kingdom of Loango / Phyllis M. Martin -- The Kingdom of Kongo / John K. Thornton -- European images of the Kongolese in books / Josiah Blackmore -- Out of Kongo and into the Kunstkammer / Alisa LaGamma -- Kongo female power / Alisa LaGamma -- Mangaaka / Alisa LaGamma.
Published in conjunction with an exhibition of the same name held at The Metropolitan Museum of Art, September 18, 2015-January 3, 2016.
"A landmark presentation that will radically redefine our understanding of Africa's relationship with the West, Kongo: Power and Majesty, opening at The Metropolitan Museum of Art this September, will focus on one of the continent's most influential artistic traditions, from the earliest moment of direct engagement between African and European leaders at the end of the 15th century through the early 20th century. The creative output of Kongo artists of Central Africa will be represented by 134 works drawn from more than 50 institutional and private collections across Europe and the United States, reflecting five hundred years of encounters and shifting relations between European and Kongo leaders. From a dynamic assembly of 15 monumental power figures to elegantly carved ivories and finely woven textiles, the exhibition will explore how the talents of Central Africa's most gifted artists were directed toward articulating a culturally distinct vernacular of power."--Metropolitan Museum of Art website
Includes bibliographical references (pages 295-300) and index.
Keywords: Art, Kongo -- Exhibitions; Art, Kongo -- Influence -- Exhibitions; Art -- Kongo Kingdom -- Exhibitions; Art -- Africa, Central -- Exhibitions; Africa, Central -- Foreign relations -- Europe -- Exhibitions; Europe -- Foreign relations -- Africa, Central -- Exhibitions; Exhibition catalogs; Exhibition catalogs